Elaboración de una guía de buenas prácticas de manufactura (BPM) para la producción de panela en la asociación de productores agropecuarios del Municipio de Inza y TierraDentro (Proagromit) (2020)
The purpose of this research work was to prepare a guide to good manufacturing practices (GMP) for the production of panela in the Association of Agricultural Producers of the Municipality of Inza and Tierradentro (PROAGROMIT) from resolution 779 of 2013 and decree 3075 1993; Panela is considered a food of high importance for Colombian households and at an economic level; the problems addressed in this project stemmed from the need to implement BPM in the association; to facilitate the process or implementation process thereof; The objectives set include the identification of the macro processes, the diagnosis of the BPM compliance status in the association and the design of the guide; The methodology used to achieve this study was descriptive, cross-sectional, and resulted in the preparation of the final guide.